Teacher training programs at vale do Acaraú State University:contribuitions to reflections about interiorization of higher education - Adriana,; Virginia Célia Cavalcante de, (Uni-pluriversidad, 2020)
Although the interiorization of Higher Education is often spoken as a synonym for its expansion, we understand that it deserves a more accurate analysis in view of its developments. In this sense, we aim in this article to problematize the idea of interiorization of higher education defended by the decentralization policy of the Vale do Acaraú State University (UVA) started with the offer of special teacher training programs based on the National Education Guidelines and Bases Law (BRAZIL, nº 9394/1996). Our studies were anchored in the analysis of official documents issued by the State Council of Education of Ceará, the regulatory body of UVA, in the analysis of institutional documents, in the analysis of the content of the speeches given by the President of the institution and in interviews with co-managing partners. who participated in the operationalization of the programs. Based on these sources, it was possible to identify the driving elements of the institutional decentralization policy and its operational dynamics. We understand that the teacher training programs offered by UVA did not contribute to the strengthening of the interiorization of Higher Education due to the absence of a contextualized, regionalized teacher training policy based on pedagogical principles beyond the demand for certification and the absence of planning institutional strategic that would make it possible to monitor and evaluate experimental training processes.